An Empirical Study of Text Books Published for Secondary Education - Hamna, M.M.A.; Sureshkumar, S. (University of Jaffna, 2025)
Adapting English Language instruction that reflects Sri Lankan context incorporating local vocabulary, cultural references, real life situations and issues relevant to Sri Lankan students rather than relying solely on generic English teaching methods that might not resonate with their experience can be understood as localizing teaching of English Language in Sri Lanka. The researchers focus on accelerating Sri Lankan vocabulary and idioms, culturally relevance examples, addressing linguistic diversity with cultural aspects that can tailor the learning materials through community engagement, individual engagement to improve comprehension, communication skills. There is a big gap in utilizing learning materials and methodology that can reflect Sri Lankan context since English has been legally announced as a second Language but practically it acts as a Lingua Franca. The text books have an imbalance diversity in its content to promote equity, inclusiveness and authenticity. The research really develops teacher capacity to adapt curriculum and navigate different dialect variations of English spoken within Sri Lankan Classrooms. Localizing the teaching of English can motivate three dimensional automations; learner, teacher, and learning autonomy that supports personalized learning reflecting socio cultural identity. This negotiation is a boost for automatizing the low-capacity learners. The researcher selected 20 classrooms from Valikamam zone, Jaffna and 10 classrooms from Katpity, Puttalam. This is mix-method research and the study can be useful to automatize the ESL practitioners of Sri Lanka to practice differentiated instructions to develop the text books according to the socio-cultural background. ELT practitioners and researchers can address linguistic diversity for ensuring localized use of English to ensure inclusive education.
Keywords: Linguistic diversity; Cultural references; Community engagement; Different dialect variation